Changes in physio‐biochemical metabolism, phenolics and antioxidant capacity of different Chinese pea varieties during germination. (20th November 2022) - Wang, Jing; Ma, Yan; Huang, Xianqing; Song, Lianjun; Li, Ning; Cheng, Yongxia; Shen, Yue; Li, Qian; Li, Tiange; Hai, Dan
Summary: In this study, changes in physiological and biochemical metabolism, phenolics and antioxidant capacity of six different Chinese pea varieties during germination were investigated. Results showed that germination had a positive effect on the physiological indexes and bioactive substances of pea. The bud length, root length, fresh weight and respiration rate of pea sprouts increased with germination time. The content of free and bound phenolics in germinated peas increased significantly. Meanwhile, activated phenylalanine ammonia‐lyase (PAL), cinnamate 4‐hydroxylase (C4H) and 4‐coumaric acid coenzyme A ligase (4CL) led to the accumulation of phenolics. Antioxidant capacity of pea sprouts increased with the extension of germination time. From the perspective of principal component analysis, compared with the other five varieties, Longwan 7 can be distinguished by free phenolic content in the later stage of germination. The result provides a new perspective for further development of pea as a functional food for human consumption. Abstract : Germination enhanced the phenolic accumulation by upregulating the enzyme activities of PAL, C4H and 4CL involved in phenolic biosynthesis, which contributed to the improvement of antioxidant capacity of pea sprouts.